(untitled) (Research, Society and Development, 2025)
The increase in life expectancy brings with it numerous illnesses, such as chronic disorders, which reduce the quality of life of this population and may interfere with mental health. To investigate and understand the relationship between chronic diseases in the elderly and mental health problems. This is an integrative literature review, in which article selection was carried out using the descriptors: “Chronic disease,” “Mental health,” “Public health,” and their equivalents in the following databases: Biblioteca Virtual em Saúde (BVS), SciELO, and Medical Literature Analysis and Retrieval System Online (PubMed). The inclusion criteria were: primary articles, full-text availability, written in English, Portuguese, or Spanish, and thematic relevance. The initial search resulted in 1,429 publications, which underwent the following screening process: application of inclusion and exclusion criteria, reading of titles, abstracts, and full texts. In the end, 9 articles were included, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. An association was observed between chronic diseases, quality of life, and mental health in elderly individuals with more concerning comorbidities, such as cardiovascular and cerebrovascular conditions. Moreover, certain factors, such as social context and awareness of physical condition, were found to aggravate the situation. If not properly addressed, these conditions may lead to suicide. This integrative review aimed to highlight the relationship between chronic diseases and mental health in the elderly, revealing that the presence of such comorbidities may accelerate the process of psychological illness.